Mentor–mentee interactions in the practicum: Whose/Who’s learning? - Díaz Maggioli, Gabriel (Argentinian Journal of Applied Linguistics - ISSN 2314-3576, 2022)
The present paper reports on a small-scale naturalistic research pilot project seeking to explore and understand the kinds of learning which ensue from the interaction between cooperating teachers acting as Mentors and student teachers during their practicum in Uruguayan State Schools. Through the use of a structured questionnaire to a randomly selected group of participants (both Mentors and Mentees), the researcher has tried disclose themes that impinge on learning from the Mentor-Mentee interaction. This study was a pilot intended as fodder for a more in-depth analysis of the Mentoring situation in Uruguay, as the country prepares to expand the mentoring model to in-service teacher development. Data were coded making reference to Wang and Odell’s (2002) perspectives towards Mentoring and a tentative explanation of the learning stemming from the interaction was attempted. Also, implications for further research and practice are outlined.